Laboratory evaluation of an indigenous developed light weight deflectometer as a quality control tool for pavement construction. (2022) - Gunde, Raj; Adepu, Ramesh; Rachakonda, Pranavi; Ch, Nageshwar Rao
Abstract: The mechanistic empirical pavement design concepts are largely based on the theory of elastic layers, and the design is assessed with the characterization of materials used in pavement construction. The present density-based quality assurance (QA) apparatus and its procedures are not effective in measuring the resilient modulus of compacted pavement layers. However, the use of high-cost field apparatus such as nuclear density gauges (NDG) is also encouraging the search for an alternative procedure. This article aims at the measurement of pavement surface modulus directly in the field using a low-cost laboratory developed Indigenous Light Weight Deflectometer (ILWD). The developed ILWDs will be employed for pavement construction QA for interpreting the stiffness of compacted pavement layers. The study was performed on the National Highway-161 in Sivampet, Sangareddy district, Telangana state. The laboratory developed ILWD was validated using the available Light Weight Deflectometer (LWD), Dynatest make, and layer modulus was also computed using a Dynamic Cone Penetrometer (DCP). The DCP was also fabricated in the laboratory as per the Transportation Research Laboratory (TRL), UK. The ILWD and DCP were used to ensure the stiffness characteristics like elastic and dynamic modulus. The field and lab test results indicate that the calculated elastic modulus and stiffness characteristics are close to each other layer moduli for the different pavement layers considered in the study, like sub-grade and granular sub-base (GSB). It is also observed that the test results from the field and laboratory have a good measure of statical correlation among the different stiffness values, and hence the developed ILWD is suitable for pavement compacted layer investigation as quality control.